2014
DOI: 10.1093/infdis/jiu014
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Vaccine Candidate Is Highly Attenuated and Protects Nonhuman Primates Against Telemetrically Monitored Disease Following a Single Dose

Abstract: Chikungunya virus (CHIKV) is a mosquito-borne alphavirus that causes major epidemics of rash, fever, and debilitating arthritis. Currently, there are no vaccines or antivirals available for prevention or treatment. We therefore generated 2 live-attenuated vaccine candidates based on the insertion of a picornavirus internal ribosome entry site (IRES) sequence into the genome of CHIKV. Vaccination of cynomolgus macaques with a single dose of either vaccine produced no signs of disease but was highly immunogenic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 33 publications
2
82
1
1
Order By: Relevance
“…To evaluate whether the vaccinated animals in this study were protected from CHIKV infection, we determined the plasma viral load immediately after challenge with a dose of CHIKV close to 100 times the 50% Animal Infectious Dose (AID 50 ). LR-CHIKV infection of cynomolgus macaques typically results in plasma viremia that peaks at day 2-3 after challenge (13,15). Consistent with this, we found that all control animals that had received only saline displayed high peak viremia that declined, reaching undetectable levels by day 10 after challenge ( Figure 6A).…”
Section: Resultssupporting
confidence: 80%
“…To evaluate whether the vaccinated animals in this study were protected from CHIKV infection, we determined the plasma viral load immediately after challenge with a dose of CHIKV close to 100 times the 50% Animal Infectious Dose (AID 50 ). LR-CHIKV infection of cynomolgus macaques typically results in plasma viremia that peaks at day 2-3 after challenge (13,15). Consistent with this, we found that all control animals that had received only saline displayed high peak viremia that declined, reaching undetectable levels by day 10 after challenge ( Figure 6A).…”
Section: Resultssupporting
confidence: 80%
“…This modification decreases the expression of viral structural proteins (184,185), which attenuates replication in mammalian cells and prevents replication in mosquito cells, as the IRES is not functional in insect cells (184). The CHIKV/IRES vaccine is safe, highly immunogenic, and efficacious in mice and NHPs (184,185), while remaining attenuated (186). nature of CHIKV disease and its associated economic burden are important considerations for the development of specific treatments.…”
Section: Prospective Chikv Treatments and Vaccinesmentioning
confidence: 99%
“…More CHIKV vaccine candidates are in preclinical studies (Schwameis et al, 2016). CHIKV-IRES vaccine, achieved by inserting a picornavirus internal ribosome entry site (IRES) into the CHIKV genome, exhibited high immunogenicity and produced no signs of disease in nonhuman primates (Roy et al, 2014). DNA vaccine utilizes a plasmid encoding CHIKV structure protein or full-length sequence from an attenuated CHIKV clone 181/25 was shown to activate immune responses in mice, without causing joint swelling, and induced long-lived protective antibodies (Hallengard et al, 2014;Tretyakova et al, 2014).…”
Section: Vaccine Research and Developmentmentioning
confidence: 99%